The Effect of Tax Aggressiveness, Firm Size, and Profitability on Corporate Social Responsibility Disclosure in Mining Companies - Anggraini, Dwi Retno; Dura, Justita (CV. Inara, 2021)
In mining companies, exploitative behavior and a lack of sense of responsibility towards the environment will threaten the sustainability of the availability of natural resources, and cause disharmony in relations with the community around the company. So it is important for mining companies to carry out social responsibility towards the environment and the community around the company so that the natural resources needed are still available. This study was conducted to determine the effect of tax aggressiveness, firm size, and profitability on corporate social responsibility disclosure in mining companies listed on the IDX. In this study CSR Disclosure is measured by disclosure criteria based on GRI indicators, tax aggressiveness is measured by income tax expense and profit before tax, Firm Size is measured using total sales, profitability is measured by the ROA (Return On Asset) indicator. This study uses quantitative methods. The population selected was 44 companies, for 2 years in 2018-2019 using the purposive sampling method, in order to obtain a sample of 15 companies that met the criteria. Data were analyzed using multiple linear regression. The results of this study indicate that tax aggressiveness has a effect on CSR Disclosure, while firm size and profitability have a negative effect on CSR Disclosure.